Morphofunctional characteristic of gastric adipocytes in patients with type 2 diabetes mellitus - Ashot Musaelovich Mkrtumyan; I V Maev; K I Bairova (Сахарный диабет)
Aim. To measure gastrointestinal hormones in plasma, evaluate morphofunctional state of G- and beta-cells in patients with gastric pathology and concomitanttype 2 diabetes mellitus (DM2). Materials and methods. A total of 84 patients with gastric ulcer (GU) and chronic gastritis (CG) were available for observation including 46 with DM2.Semi-quantitative evaluation of stomach infection by H.pylori. was performed by a histological method. Stained G- and beta-cells were counted under 400xmagnification in 10 fields of vision for each medicinal preparation used in the study. Chromogranin A, somatostatin, and gastrin were detected by immunohistochemicalmethods, gastrin-17 and somatostatin-14 by the respective immunoassays. Control group comprised 10 practically healthy volunteers. Results. Patients with combined GU (or CG) and DM2 pathology had smaller density of G- and beta-cells, lower plasma gastrin and somatostatin levelsthan those without DM2 (p